2018
DOI: 10.1101/gad.319418.118
|View full text |Cite
|
Sign up to set email alerts
|

Repairing the lungs one breath at a time: How dedicated or facultative are you?

Abstract: Tissue regeneration involves various types of cellular and molecular responses depending on the type of tissue and the injury or disease that is inflicted. While many tissues contain dedicated stem/progenitor cell lineages, many others contain cells that, during homeostasis, are considered physiologically functional and fully differentiated but, after injury or in disease states, exhibit stem/progenitor-like activity. Recent identification of subsets of defined cell types as facultative stem/progenitor cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…Multiple stem or progenitor cells are required for maintaining lung functions during normal condition and repair. The maintenance and repair of epithelium at different regions mainly depend on its resident stem or progenitor cells [1][2][3] .…”
Section: O R R E S P O N D E N C E O P E N a C C E S Smentioning
confidence: 99%
“…Multiple stem or progenitor cells are required for maintaining lung functions during normal condition and repair. The maintenance and repair of epithelium at different regions mainly depend on its resident stem or progenitor cells [1][2][3] .…”
Section: O R R E S P O N D E N C E O P E N a C C E S Smentioning
confidence: 99%
“…In contrast to some other tissues that show very high rates of turnover, such as the hematopoietic system and the intestinal tract, the turnover of lung tissue is relatively slow, with a turnover time of 7 yr in humans. However, upon injury, the tissue has the capacity to quickly repair the damage through the mobilization of resident cells with tissue stem cell properties (Rawlins and Hogan 2006;Kim 2017;Leach and Morrisey 2018;Lee and Rawlins 2018). These specialized cells, such as basal cells and subsets of alveolar type II (AT2) cells, are capable of giving rise to the diverse lineages that line the different anatomical compartments of the respiratory system.…”
Section: Epithelial Lineages In the Lungmentioning
confidence: 99%
“…Recent evidence shows that individual AT-II Axin2+ stem cells reside in single-cell fibroblast niches providing juxtacrine Wnt signaling that maintains them as stem cells during homeostasis [43]. Lung injury induces the secretion of autocrine Wnt, allowing proliferation in response to mitogens and expansion of the progenitor pool [43,44]. It has been suggested that the inability of exhausted AT-II to trans-differentiate into AT-I and to regenerate the epithelial layer after continuous damage may cause aberrant activation of the physiological signaling pathways upstream of this process [10,16,45], which eventually leads to fibrosis.…”
Section: The Role Of Emt In Idiopathic Pulmonary Fibrosismentioning
confidence: 99%